Training and Assistance in Preparing Class Action Research Proposals for Science Teachers in Hulu Sungai Tengah Regency - Dewi Dewantara; Zainuddin Zainuddin; Mustika Wati; Suyidno Suyidno; Misbah Misbah; Surya Haryandi; Panji Rahmattulah; M Jiddan Mishbahul Munir (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This article has a focus on describing the effectiveness of the training and assistance in preparing class action research proposals for science teachers in Hulu Sungai Tengah Regency. This training activity took place at SMPN 10 Barabai, which was attended by 36 science / science teachers in Hulu Sungai Tengah Regency. The effectiveness of training and mentoring can be seen from the achievements of teachers as seen from the pretest and posttest. The results of the pretest and posttest were tested whether there was a significant difference between the pretest and posttest values using the paired sample t-test. If the paired sample t-test results indicate significant differences between the pretest and posttest values, then proceed with the N-gain test. The effectiveness of the conclusion is the training and assistance in preparing class action research proposals for science teachers in the Hulu Sungai Tengah Regency in the high category. Thus, it is recommended that further training be carried out related to writing class action research reports. This kind of training is also needed for teachers in other regions, as well as in other subjects.